2012
DOI: 10.1074/jbc.m112.362996
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interactions between NFATc1 (Nuclear Factor of Activated T Cells c1) and STAT-3 (Signal Transducer and Activator of Transcription-3) Mediate G Protein-coupled Receptor Agonist, Thrombin-induced Biphasic Expression of Cyclin D1, with First Phase Influencing Cell Migration and Second Phase Directing Cell Proliferation

Abstract: Background: NFATc1 and STAT-3 associate with each other constitutively and regulate cyclin D1 expression in response to thrombin, a G protein-coupled receptor agonist. Results: NFATc1 exists in complex with STAT-3 and modulates its acetylation via recruiting p300 in the biphasic expression of cyclin D1 facilitating VSMC migration and proliferation. Conclusion: NFATc1-STAT-3 cooperatively binds to cyclin D1 promoter and modulates its activity. Significance: NFATc1-STAT-3 interactions may play a role in vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…2E), which confirms the role of STAT1 in CD36 induction by 15(S)-HETE. Previously, we have demonstrated that p300 mediates STAT3 acetylation in the induction of cyclin D1 expression by thrombin (31). Therefore, to understand the mechanisms of STAT1 acetylation by 15(S)-HETE, we studied the role of p300.…”
Section: Resultsmentioning
confidence: 99%
“…2E), which confirms the role of STAT1 in CD36 induction by 15(S)-HETE. Previously, we have demonstrated that p300 mediates STAT3 acetylation in the induction of cyclin D1 expression by thrombin (31). Therefore, to understand the mechanisms of STAT1 acetylation by 15(S)-HETE, we studied the role of p300.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a role for CDKs in cell migration has also been reported (42). We have demonstrated previously that NFATc1, via enhancing cyclin D1 expression and, thereby, CDK4 activity, mediates both platelet-derived growth factor BB and thrombin-induced VSMC migration and proliferation (20,34). In addition, we showed that NFATc1-dependent cyclin D1/CDK6 activity is required for phosphorylation and activation of a Rho GTPase effector PKN1 in mediating chemokine CCL2-induced HASMC migration and proliferation and injury-induced vascular wall remodeling (22).…”
Section: Discussionmentioning
confidence: 99%
“…2, G and H) (21). In addition, our previous work showed that NFATc1 mediates cyclin D1 expression in response to various agonists, including MCP1 (20,22,34). Therefore, we next tested the role of NFATc1 and cyclin D1 in MCP1-induced Pak1 phosphorylation/activation.…”
Section: Cdk6 and Cdk4 Mediate Mcp1-induced Pak1 Activation-mentioning
confidence: 99%
“…Moreover, NFAT2 constitutive activation induces autocrine of growth factors, which can activate STAT3 in turn [110]. Interestingly, nuclear NFAT2 can cooperate with STAT3 to control IL-6, IL-4 and other cytokine expressions [111]. This feedback loop promotes cancer cell survival under stress, such as anti-cancer drug treatment.…”
Section: Nfats In Tumor Survival and Drug Resistancementioning
confidence: 98%